Conflicts politics construction privacy obsession material on the work of Christian Kerez = Materialien zur Arbeit von Christian Kerez - Kerez, Christian (Hatje Cantz, 2008)
Exhibition catalog including summaries, plans and photographs of four projects by architect Christian Kerez: House with one Wall, Zurich; Museum of Modern Art, Warsaw; School Building Leutschenbach, Zurich; and Apartment Building Forsterstrasse, Zurich. Includes foreword by Moritz Küng and essays by Hubertus Adam, Marcel Andino Velez, Tibor Joanelly, and Hans Frei.